Food Safety on the Farm: Good Agricultural Practices and Good Handling Practices – Traceback - Alexandra Chang; Alina Balaguero; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS)
FSHN10-04, a 3-page fact sheet by Alexandra Chang, Alina Balaguero, Renée Goodrich-Schneider, and Keith R. Schneider, is part of the Food Safety on the Farm series and discusses the need for traceback requirements to identify and eliminate sources of microbial hazards, outbreaks, and food contamination. Includes references. Published by the UF Department of Food Science and Human Nutrition, June 2010.